2019
DOI: 10.1155/2019/3470390
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Software-Defined Technologies for Underwater Acoustic Sensor Networks: A Survey

Abstract: Underwater Acoustic Sensor Networks (UASNs) are an important technical means to explore the ocean realm. However, most UASNs rely on hardware infrastructures with poor flexibility and versatility. The systems typically deploy in a redundant manner, which not only leads to waste but also causes serious signal interference due to multiple noises in designated underwater regions. Software-Defined Networking (SDN) is a novel network paradigm, which provides an innovative approach to improve flexibility and reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 116 publications
0
14
0
Order By: Relevance
“…Therefore, an UWSN framework supporting heterogeneous communication of various hardware is needed. Most of the existing underwater multi-mode communication frameworks are based on the adaptation layer, and need a special routing algorithm to support, but cannot achieve the versatility, re-programmability and transparency of multi-mode communication [7][8][9][10][11][12][13][14]. The routing and forwarding of traditional UWSN depends on the node address.…”
Section: Difficult Communicationmentioning
confidence: 99%
“…Therefore, an UWSN framework supporting heterogeneous communication of various hardware is needed. Most of the existing underwater multi-mode communication frameworks are based on the adaptation layer, and need a special routing algorithm to support, but cannot achieve the versatility, re-programmability and transparency of multi-mode communication [7][8][9][10][11][12][13][14]. The routing and forwarding of traditional UWSN depends on the node address.…”
Section: Difficult Communicationmentioning
confidence: 99%
“…The experiment revealed that it had advantages in the end-to-end delay, the surviving time, and coverage. J. Wang et al [30] made a comprehensive investigation of SDN and analyzed the progress of softwaredefined underwater networks.…”
Section: B Advances In Software-defined Uans 1) Advancement In the Amentioning
confidence: 99%
“…Most of these algorithms implement based on the residual energy and other constraints, and adopt the transmission of multi-hop mode. Nevertheless, none is SDN-driven type [80], [81]. To the best of our knowledge, it is the first paper to introduce the clustering of UASNs based on SDN.…”
Section: Progress Of Clustering Technologiesmentioning
confidence: 99%